The Mediation Effect of Work Motivation on the Relationship Between Training Opportunities and Job Performance: A Lesson from Employees in Manufacturing Firms in Tanzania (Tanzania Journal for Population studies and Development, 2025)
In any organization, the quality of its human resources (employees) and the effectiveness of its training programmes in upgrading skills and knowledge of human resources are key to performance. Increased business competition has resulted in consumers demanding quality products and services. This has forced organizations to focus on the competence of their employees to meet customer demand to improve business performance. The objective of this study is to examine the mediation effect of work motivation in training opportunities and employee job performance relationship. The survey used a sample size of 139 employees from a manufacturing company in Tanzania to study this relationship. SmartPLS4 was used to analyse the data collected. The finding of the main effect indicates that training opportunities significantly influences employee job performance. The findings on the mediation effect show that work motivation fully mediates the nexus of training opportunities and job performance. Theoretically, the findings provide additional evidence that work motivation mediates the nexus between perceived training opportunity and job performance; while practically, an effective training programme improves employees’ working skills, knowledge, experience, and attitude for better job performance. Thus, employee work motivation largely leads to positive outcomes on employee job performance.